Improvement of the Environment and Health in Terms of Governance of Slum Settlements through Collaboration Between Stakeholders - Rainfil Rainfil (Pusat Studi Pembangunan dan Pemberdayaan, 2022)
Slum settlements are the subject of this research, specifically how better stakeholder collaboration can lead to better environmental and health outcomes. The study's objectives are to (1) evaluate the effectiveness of stakeholder cooperation in improving the health of slum residents, (2) identify the obstacles to and opportunities for enhancing the environment and health of slum communities, and (3) assess the environmental and health conditions in slum settlements. Access to essential services and infrastructure, environmental pollution, and healthcare availability were all summarized using descriptive statistics. The findings emphasize the immediate need for comprehensive and collaborative approaches to tackling the pressing issues of poor living conditions and limited access to healthcare in slum settlements. Stakeholder collaboration, including that between the government, NGOs, CBOs, and the business sector, is also highlighted as being essential to improving slum dwellers' health and wellbeing. It was also determined that community-led projects, multi-sectoral approaches, and innovative solutions are essential to enhancing the quality of life in informal settlements and reducing health risks. Finally, the research highlights barriers to enhancing the environment and health of slum settlements, such as inadequate access to basic services, pollution, and economic and social exclusion. Taken as a whole, the results of this research stress the critical importance of multidisciplinary efforts to alleviate slums' myriad problems. Sustainable improvements in the environment and health of slum settlements can be achieved through the implementation of innovative solutions and the promotion of cooperation among stakeholders, lowering the disease burden in these communities and fostering social and economic inclusion.